Addressing Problems in Reporting and Classification of Complications in Neurosurgery - Riabec, Pavel; Šustickas, Gytis (Lietuvos chirurgija, 2022)
Objective. The purpose of this study was to quantify the rate of adverse events associated to in neurosurgery interventions, to evaluate the differences in reporting of such events among different authors and reviews, and to find the reason behind the occurrence of this differences. Methods. A systematic literature review of scientific publications on existing classifications and reports of frequency on complications in neurosurgery was performed by analysing articles from international databases. Results and conclusion. This current overview is taking an outlook on the existing issues in the classification and reporting of complications in neurosurgery. Complications are common in neurosurgery. Because of nonuniform criteria, unstandardized data gathering procedures, and retrospective data collection, their reporting is inconsistent and varies considerably among authors and reviews. The best way to address this issue is by gathering prospective, multi-institutional outcomes data on neurosurgical patients. The data collection initiatives in the future should be using same terminology and be based on the same universally accepted criteria.